Epigenetic regulation of cancer in response to chemotherapy - Landry, Joseph W.; Fisher, Paul B. (Academic Press, 2023)
Epigenetic Regulation of Cancer in Response to Chemotherapy, Volume 158 of the Advances in Cancer Research series, highlights new advances in the field, with this new volume presenting chapters on timely topics, including Epigenetically Programmed Resistance to Chemotherapy and Promotion of Immune Evasion in Cancer, A Role for the Epigenome in Cancer Cell Drug Tolerance, Histone Methylation and X Chromosomal Genes in Metastasis of Breast Cancer, Targeting Epigenetic Regulation Using Small Molecule Inhibitors, Histone Deacetylase Inhibitors as Sanguine Epigenetic Therapeutics against Pugnacious Lung Cancer, From ecology to oncology: To understand cancer stem cell dormancy, ask a Brine shrimp (Artemia), and more. Additional chapters cover Predictive Models of Chemoresistance Generated by Crunching the Public Drug Screen, Epigenomic and Genomic Profiling Datasets via Regression-, Machine Learning, and Knowledge-Based Methods, Probing on the Mechanisms of lncRNAs on Cancer Drug Resistance, Drug Tolerant Persister Cells in Cancer: Current Knowledge and Therapeutic Perspectives, and much more.